Is orthodontic treatment a risk factor for temporomandibular disorders? - Tomas Magnusson; Antonio Sérgio Guimarães (Dental Press Journal of Orthodontics, 2012)
INTRODUCTION: The possibility that orthodontic treatment in childhood might be a risk factor for the development of temporomandibular disorders (TMD) later in life has been an issue of great controversy in dental literature. OBJECTIVE: To determine a possible negative or positive correlation between orthodontic treatment and TMD by presenting the results and conclusions from a number of key-papers dealing with this subject. RESULTS AND CONCLUSION: According to current knowledge, there is no scientific evidence to support that orthodontic treatment is a risk factor for the development of TMD. On the other hand, there is some evidence to support that a proper orthodontic treatment performed in childhood might have a positive effect upon the functional status of the masticatory system later in life.